Quality indicators for the production and assessment of podcasts’ episodes - Bottentuit Junior, João Batista (2008)
In this paper we begin by weighing the importance that the access to information assumes nowadays and, at the same time, the growing need of people to fulfill the time spent getting to and from their workplace. Afterwards we made an approach to the podcast’s concept comparing its educational potentialities, specially the role it can play in granting the user the access to “mobile” training modalities at anytime and in anyplace. Finally, concerning the podcasts’ episodes quality available on the web, we have decided to develop a set of recommendations at five levels, based on a bibliographic revision – general, introduction, content, conclusion and group work – that can improve the production quality of podcasts’ episodes, making them clearer and more effective towards the promotion of learning.